A review on the unexplored and underutilized Arenga species in India - Pillai, Arun R.; Riyas, C.T.; Sabu, K. K. (Current Botany, 2021)
The Genus Arenga which includes some of the magnificent palms of the world, their multipurpose utility and diversity is been reviewed to shed light on the wide potentialities of the different species. Of the 24 species reported only few of them has been recognized as candidates for domestication from the wild. Four species namely Arenga pinnata, A. obtusifolia, A. micranta and A. wightii have been reported from India. Their ecological aspects, utilization and conservation strategies of the tribal communities have been discussed. Seed biology of few species has been reviewed along with the available data generated through scientific studies. Although most of the members in this Genus have the potential to be explored commercially, they still fall into the underutilized category. The review is mainly intended to highlight the untapped resources from different species in this Genus which will promote more scientific studies and result in proper conservation and sustainable utilization of these valuable palms.